Keberlanjutan Bisnis Di Industri Makanan dan Minuman: Studi Struktur Modal, Profitabilitas, dan Pertumbuhan Perusahaan Selama Masa Pandemi - Asna Shofia; Ana Kadarningsih (International Forum of Researchers and Lecturers, 2023)
This research aims to analyze the impact of capital structure, profitability and company growth on company value during the pandemic in beverage and food companies verified on the IDX. This study had a population of 90 companies from December 2019-June 2023. To collect samples in accordance with the requirements, a purposive sampling strategy was applied, 25 companies met the sample collection criteria and a total of 200 data were processed. Descriptive statistical analysis, traditional assumption tests, multiple linear regression testing, and hypotheses are all used in the research analysis approach. The analysis tool uses IBM SPSS version 26. The results of the study show that the structure and partial independent variables have a positive and significant impact on company value. Partial profitability has a positive and significant impact on company value and partial company growth does not have a significant impact on company value. The results of all independent variables simultaneously have an impact on company value.